Problematika Pengembangan Wakaf Uang Melalui Koperasi Syariah di Era 4.0 - Inne Risnaningsih; Siti Nurhayati (Jurnal Co Management, 2020)
Research was conducted to elaborate the development problematics through sharia cooperative as the Sharia financial institution of Waqf money (LKS PWU) in the 4.0 era. The potential waqf of money is not yet rolled out and the maximum benefit is so that waqf of money has not been able to contribute significantly to national development. This research is a qualitative research (qualitative research) that is descriptive normative that is the depiction of the true state based on data obtained either through literature studies and field studies associated with existing laws and regulations. The results concluded that the existence of sharia cooperative in its role as LKS PWU is indeed quite well established with the support of existing legislation with the record of continuing the Repair process (Amendment) to support the development of waqf productivity. However, at the level of practice, it turns out that the authority is not fully usable, so mathematically the potential of waqf money so large has not been maximally absorbed by the LKS PWU on sharia banking institutions and sharia cooperatives where the level of literacy and community inclusion regarding Waqf money is very low plus the preference of community in choosing Sharia cooperative as LKS PWU is also very low so it takes integrated effort involving all stakeholders in raising these three qualifications and The Waqf law to better accommodate the role of LKS PWU including sharia cooperative in bridging the community to Waqf.